The Success of the Social Assistance Program in Supporting the Economic Resilience of Poor Communities during the Covid-19 Pandemic - Runi, Naila Ananda; Manik, Citra Wulandari; Aini, Lathifah; Situmorang, Rachel Meylani; Salsabila, Sasabila; Sari, Yolanda Novita; Nasution, Armin Rahmansyah (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
Poverty is a multifaceted problem that impacts people's lives in many ways, such as socio-cultural, educational, religious, and economic. Poverty has increased as a result of the COVID-19 epidemic in various countries, including Indonesia. The Indonesian government has responded by introducing a number of social assistance initiatives to help those affected by the pandemic. The purpose of this study is to assess how well social assistance programs are helping the underprivileged maintain their financial stability during the COVID-19 pandemic. The study, conducted in Binjai City, Indonesia, centered on the Direct Cash Transfer (BLT) initiative. The findings of this study show that the social assistance program had a beneficial and lasting impact on the local economy of Binjai City. Increases in community consumption, demand for goods and services, production, employment, and economic growth demonstrate this.